Predictors of Perceived Caregiving Burden Among Caregivers of Older Hemodialysis Patients - Mahdie Taherkhani; Fatemeh Mohammadi; Farnoosh Rashvand; Seyedeh Ameneh Motalebi (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives: Elderly patients are the largest and fastest growing group of patients under dialysis and their caregivers are faced with high burden care. Therefore, the present study was conducted to determine the predictors of caregiver burden among caregivers of older patients under hemodialysis residing in Qazvin province, Iran. Methods & Materials: This cross-sectional study was conducted on caregivers older patients under hemodialysis in 2020. The caregivers were selected by census method among eligible caregivers of older patients under hemodialysis referring to dialysis centers of Qazvin Province, Iran. Data were collected using the demographic checklists, Zarit Burden Interview (ZBI) in Care, Bartell Scale, Multidimensional Scale of Perceived Social Support (MSPSS), General Self-Efficacy Scale (GSE), and Religious Coping Scale (RCOPE). The collected data were analyzed by a multivariable regression model in SPSS software v. 23.  Results: The mean and standard deviation of the age of 252 caregivers and older patients were 44.9±13.16 and 69.4±7.7 years old, respectively. The results of multivariate analyses showed that significant predictors of caregiver burden were perceived social support (β=0.333, P<0.05), disability (β:-0.137, P<0.05), health status (β=0.154, P=0.010), and financial level (β=0.154, P=0.010). As the caregiver burden was decreased by increasing the social support and decreasing the rate of disability. Furthermore, the caregivers with higher financial levels and better health status reported lower caregiver burden. Conclusion: It can be concluded that enhancement of social support and more attention to the health of caregivers as potential patients are important factors for reduction of caregiver burden care.